Increase in Equilibrium Price by Fast Oscillations. (20th May 2014) - Ahmad, Babar; Mahr, Khalid Iqbal
Abstract : The dynamics of a market can be described by a differential equation. Using the concept of fast oscillation, the system (typical market) can also oscillate around a new equilibrium price, with an increase. Previously that increase was established by applying harmonic force. In present work, harmonic force is replaced by an arbitrary periodic force with zero mean. Hence the increase in equilibrium price can be controlled by varying the external arbitrary periodic force.